(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Victorian literature served as an essential mirror of the profound social transformations occurring in nineteenth-century Britain. Among the era’s most prominent authors, Charles Dickens used his novels as vehicles to reveal the struggles faced by the lower classes, the injustices created by industrial expansion, and the moral tensions that accompanied the rise of modern urban life. In works such as Oliver Twist, Hard Times, and Bleak House, Dickens portrays the realities of exploitation, poverty, class oppression, and institutional failure with remarkable clarity. Through his richly developed characters, detailed settings, and incisive critique of societal structures, he not only documented the flaws of Victorian society but also urged readers to reflect on the need for compassion, fairness, and reform. This study examines how Dickens’s narratives operate simultaneously as artistic expressions and as critical commentaries on the social issues of the Victorian age, demonstrating the role of literature in shaping public awareness and advocating for humanitarian change.